Geologic History of the Amundsen Crater Region Near the Lunar South Pole: Basis for Future Exploration - Lukas Wueller; Wajiha Iqbal; Thomas Frueh; Carolyn H. van der Bogert; Harald Hiesinger (The Planetary Science Journal, 2024)
We provide the first detailed 1:100,000 scale geomorphologic map of the ∼100 km Amundsen crater region, which is of high scientific relevance for future exploration, e.g., NASA’s VIPER mission, the Artemis program, and the Chinese International Lunar Research Station. We investigated the complex geological history of the region before and after the formation of Amundsen crater on the rims of the South Pole–Aitken (SPA) and Amundsen–Ganswindt basins. We present a new Amundsen crater formation age of ∼4.04 Ga, which, in contrast to previously derived ages, is based on non-light-plains terrain. The estimated maximum excavation depth for Amundsen crater is ∼8 km, and elevated concentrations of FeO near the crater suggest that Amundsen may have redistributed SPA-derived materials. Plains materials of various kinds were observed both inside and outside Amundsen crater and are estimated to be up to 350 m thick and ∼3.8 Ga old. A less cratered, tens of meters thick mantling unit indicates a resurfacing event ∼3.7 Ga ago. We highlight five potential exploration sites that satisfy technical constraints (such as shallow slopes, solar illumination, and Earth visibility), provide materials that can be sampled, and are capable of addressing multiple science objectives. Due to its accessibility and traversability, combined with its geologic diversity, proximity of permanently shadowed regions for studying volatile processes, and ability to address multiple science objectives, we confirm and reinforce the Amundsen crater region as a high-priority landing and exploration site.